Gambaran Tingkat Kesadaran Emosi pada Anak Usia Dini di Panti Asuhan GA - Anjani Rahmah Suci; Nadya Serafin Aprilia Wiranto; Michelle Patricia Mustopo; Linda Wati (Pusat riset dan Inovasi Nasional, 2025)
Childhood represents a pivotal stage in every individual's development, particularly in the social and emotional domains. Young children are highly reliant on the support of their surrounding environment to recognize and manage their emotions. Indeed, emotional awareness develops progressively, commencing from physical. sensations to the capacity to comprehend complex emotions. However, children with intricate life backgrounds and a lack of parental figures tend to encounter obstacles in understanding the emotions they experience. Based on observations conducted on early childhood children at the GA Orphanage, it was found that their level of emotional awareness is still relatively low. Consequently, a structured activity-based approach was implemented to assist these children in understanding and managing their emotions.